Determinasi ROA Dan BOPO Terhadap Kecukupan Modal Pada Bank Nagari Di Kota Padang Tahun 2016-2018 - Renil Septiano; Syahdeni Pratama (JURNAL PUNDI, 2022)
The aim of this study is to analyze the influence of return on asset (ROA) and efficiency (BOPO) to Capital Adequacy Ratio (CAR) at PT. Bank Nagari in Padang year 2016-2018. Object of this study taken Bank Nagari accessed on website www.banknagari.co.id and obtained banking monthly report as much 36 data. This research classified the quantitative research. Data analysis is done by multiple linear regressions as a statistics tool. Hypotheses test used t-statistic and f-statistic at level significance 5%.Data procesing using eviews8. The result shows that ROA have a significant negativeinfluence on CAR and BOPO have a significant negative influence on CAR.. However, ROA and BOPO have a significant influence to CAR simultaneously. Based on coefficient determination showed, all independent variables have 22,70% contribution value toward CAR